The area of Interregional Law after the Regulations regarding maintenance obligations and separation and divorce - Pérez Milla, José Javier (Revista de derecho aragonés, 2018)
This research tries to establish legal rules that derive from the use, in 5 European Union Regulations on family and inheritance, of internal conflicts of laws arising between such units only clauses and the incorporation by reference of the Council Regulation 1259/2010 of 20 December 2010 implementing enhanced cooperation in the area of the law applicable to divorce and legal separation and the Hague Protocol of 23 November 2007 on the law applicable to maintenance obligations.